ANALYSIS OF COMMUNITY PARTICIPATION IN THE FOREST AND LAND REHABILITATION PROGRAM IN TOTOPO VILLAGE, BILATO SUBDISTRICT, GORONTALO REGENCY - Irwan Bempah; Radi Afriandi E; Sukirman Rahim (Lambung Mangkurat University-Indonesia, 2026)
The primary objectives of this study were twofold: to evaluate the extent of community engagement in Forest and Land Rehabilitation (FLR) initiatives and to identify the factors driving this public involvement. Adopting a quantitative research design, primary data were gathered via questionnaire distribution and subsequently analyzed using descriptive statistics alongside multiple linear regression. The empirical results demonstrated that overall community participation in the FLR program stood at 57.66%, falling into the